Methods for Optimizing the Effectiveness of Assisted Reproductive Technology Programs using Pre-Implantation Genetic Testing (Global Journal of Medical Research, 2022)
These guidelines describe a study whose purpose was to analyze the feasibility of performing genetic screening of embryos Next Generation Sequencing - NGS as part of infertility treatment cycles to determine the relationship or its absence between the stage of development of the embryo and its survival as well as an indicator of the successful development of pregnancy with the previous genetic screening Based on the results of a comprehensive study the effect of genetic screening vitrification oocyte competence and clinical indicators of patients on embryo survival was established